Scheme for Improving LKJ System Automatic Level - YANG Qing-xiang; YANG Hui-xin (机车电传动)
Present status of LKJ system application was stated, and LKJ system automatic level proving schemes were proposed with introduction of computer control priority mode, vehicle-ground transfer technology, Beidou Navigation Satellite system, wire-less communication network technology etc, which helped to rise LKJ system automation to a new level.